2006
DOI: 10.1111/j.1744-7909.2006.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping of Maize Yield and Its Components Under Different Water Treatments at Flowering Time

Abstract: Drought or water stress is a serious agronomic problem resulting in maize (Zea mays L.) yield loss throughout the world. Breeding hybrids with drought tolerance is one important approach for solving this problem. However, lower efficiency and a longer period of breeding hybrids are disadvantages of traditional breeding programs. It is generally recognized that applying molecular marker techniques to traditional breeding programs could improve the efficiency of the breeding of drought-tolerant maize. To provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 13 publications
0
20
1
1
Order By: Relevance
“…These results were unexpected based on our previous PQL study, which did not reveal any QTL for maize yield and its component in the vicinity of the ZmASR1 chromosomal region (de Vienne et al, 1999;Jeanneau et al, 2002). Nevertheless, it may be pointed out that recently identified QTLs for ear length under waterstressed conditions (Lu et al, 2006) and female flowering time (Marino et al, 2009) are centered on the ZmASR1 locus. The finding that ZmASR1-OE plants demonstrated significant improvements in ear leaf area and shoot biomass yield, as well as increases in leaf dry weight and total chlorophyll content, implies that these improvements in vegetative productivity translated into improvements in reproductive performance and kernel yield.…”
Section: Zmasr1 Maintained Kernel Yield Under Water Deficit Conditioncontrasting
confidence: 48%
“…These results were unexpected based on our previous PQL study, which did not reveal any QTL for maize yield and its component in the vicinity of the ZmASR1 chromosomal region (de Vienne et al, 1999;Jeanneau et al, 2002). Nevertheless, it may be pointed out that recently identified QTLs for ear length under waterstressed conditions (Lu et al, 2006) and female flowering time (Marino et al, 2009) are centered on the ZmASR1 locus. The finding that ZmASR1-OE plants demonstrated significant improvements in ear leaf area and shoot biomass yield, as well as increases in leaf dry weight and total chlorophyll content, implies that these improvements in vegetative productivity translated into improvements in reproductive performance and kernel yield.…”
Section: Zmasr1 Maintained Kernel Yield Under Water Deficit Conditioncontrasting
confidence: 48%
“…Many studies have identified QTL for traits relating to increased ear size in maize (Berke and Rocheford, 1995;Veldboom and Lee, 1996;Austin and Lee, 1996;Graham et al, 1997;Ajmone-Marsan et al, 2001;Lima et al, 2006;Yan et al, 2006;Sabadin et al, 2008;Lu et al, 2006Lu et al, , 2011. A total of 45 ED, 36 CD, 25 KD, and 27 KRN QTL were retrieved, but no QTL for ear size traits was found at bin 9.03 of chromosome 9 by conducting a QTL search for these traits in the Maize Genetics and Genomics Database (www.maizegdb.org).…”
Section: A Major Qtl For Ear Size In Maizementioning
confidence: 99%
“…Many studies have focused on the genetic characteristics and molecular mechanisms that affect yield, and many quantitative trait loci (QTL) for yieldrelated traits have been identified (Berke and Rocheford, 1995;Austin and Lee, 1996;Graham et al, 1997;Ajmone-Marsan et al, 2001;Lima et al, 2006;Yan et al, 2006;Sabadin et al, 2008;Lu et al, 2006Lu et al, , 2011. Because most of these QTL are minor QTL, it is difficult to utilize them for pyramiding favorable alleles.…”
Section: Introductionmentioning
confidence: 99%
“…QTL analysis has been used to detect genomic regions and QTL associated with grain yield and its component for some other crop species (Lu et al, 1997;Lu et al, 2006;Liu et al, 2008;Xue et al, 2010). In sorghum, QTL associated with yield and yield component traits have been reported recently (Shehzad & Okuno, 2015).…”
Section: Introductionmentioning
confidence: 99%